Comparison of soil classification methods among domestic and oversea based on CPTU test. Issue 3 (March 2020) - Wang, Junpeng; Wang, Bingkang
Abstract: This article presents the comparison of two soil classification methods among domestic and oversea based on CPTU test in geotechnical practice of soft deposit subgrade. Although CPTU test exists earlier in the world, However, CPTU test has been not applied in geotechnical practice of road subgrade until in recent years in China. Two soil classification methods among domestic and oversea are applied to soil classification and differences of them are analyzed.